The LOHAS (Lifestyle of Health and Sustainability) Attitude Questionnaire for Assessing Sustainable Lifestyles Among University Students - Jančaříková, Kateřina; Brůnová, Linda; Huňková, Zuzana; Marcom, Guilherme Stecca; Svobodová, Silvie; Jančařík, Antonín (Journal of Education Culture and Society, 2025)
Aim. This paper introduces the development, implementation, and pilot validation of the LOHAS Attitude Questionnaire. This instrument evaluates sustainable attitudes and behaviour among university students, based on the consumer typology model by the Natural Marketing Institute (NMI). The analysis explores the reliability and validity of the questionnaire and its capacity to identify distinct lifestyle groups and attitudes towards sustainability.Methods. The LOHAS Attitude Questionnaire was developed through a comprehensive literature review, expert consultation, and iterative pilot testing. The pilot study involved 1,089 full-time university students across three Czech universities, representing various disciplines. Data collection employed a 40-question instrument, with responses captured on a Likert scale. Statistical analyses, including Cronbach’s alpha and factor analysis, were conducted using SPSS to determine reliability and to identify latent factors.Results. The reliability analysis yielded a Cronbach’s alpha of 0.881, indicating high internal consistency. Factor analysis identified five distinct components aligning with the NMI's typology: LOHAS, NATURALITES, DRIFTERS, CONVENTIONALS, and UNCONCERNEDS. Findings suggest the questionnaire effectively differentiates lifestyle groups and provides insights into students' attitudes towards sustainability.Conclusion. The LOHAS Attitude Questionnaire proves to be a reliable and valid tool for assessing sustainable attitudes and behaviour among university students. It offers a robust framework for monitoring the impact of sustainability education and tailoring interventions based on lifestyle categories. Future research should expand its application to diverse cohorts and examine its role in fostering sustainable behaviour through targeted educational initiatives.